Pengaruh Metode Pembelajaran Quiz Team terhadap Kemampuan Kognitif Siswa pada Mata Pelajaran IPS di Kelas VIII MTS Negeri 1 Kota Blitar Tahun Ajaran 2023/2024 - Prasasti Bela Mafiroh; Bagus Setiawan (Universitas 45 Surabaya, 2024)
This research is based on problems in teaching and learning activities at MtsN 1 Blitar City. Using methods that are repeated repeatedly makes students quickly feel bored and fed up when studying. This can result in low student learning outcomes. The learning method that is often applied is using video and PPT methods without explaining first. Therefore, the researcher conducted research to explain the problem above. The aim was to find out the effect of the quiz team learning method on the learning outcomes of class VIII students at MTs Negeri 1 Blitar City for the 2023/2024 academic year in social studies subjects and to find out the learning outcomes for class VIII students at MTsN 1 City. Blitar for the 2023/2024 academic year in social studies subjects using the Quiz Team learning method. The approach used is quantitative research. This research design is Quasi Experimental. In this research the author uses data collection instruments, namely observation and learning outcomes tests. The final results of this research show that there is an influence on social studies learning outcomes with the experimental class average score being 87.5 and the control class average being only 73.875 by providing the quiz team learning method, where the KKM score is 75. This proves the application of the quiz team learning method influence on the learning outcomes of class VIII students at MTs Negeri 1 Blitar City.